EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM POSING BERBANTUAN POHON SOAL TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATERI STOIKIOMETRI DI SMA NEGERI 2 SUKADANA - Ucu Liani; Tuti Kurniati; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2019)
This study was initiated by the low learning outcomes of the tenth grade students of SMA 2 Sukadana on Stoichiometry class, especially on molarity, molality, and determining the empirical and molecular formulas. The problems are due to the lack understanding on the concept of molarity, molality, and mole fraction. Therefore, it is important to develop a learning model that can enhance student’s understanding on the concept in accordance with the character of the student and the learning material. This study aimed at investigating the effectiveness and the differences of the students learning outcomes after taught using Tree-Based Posing Problem model on molarity, molality, mole fraction, and empirical and molecular formulas. Using a quasi-experimental method, 28 tenth grade students of the MIA class participated in this study. The data collection techniques used were pre and posttests, observation, and interview. The study showed the mean score of the pretest was 40.17 and the posttest was 90.67. The result of the Effect Size obtained 0.887 which was equivalent to 31.06%. This means that there were differences of student learning outcomes after taught using Tree-Based Posing Problem model. To conclude, Tree-Based Posing Problem model is effective in enhancing students learning outcomes, especially on molarity, molality, mole fraction, and empirical and molecular formulas.